2016
DOI: 10.1016/j.chc.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Objective Testing

Abstract: Drug testing, when carefully collected and thoughtfully interpreted, offers a critical adjunct to clinical care and substance use treatment. However, because test results can be misleading if not interpreted in the correct clinical context, clinicians should always conduct a careful interview with adolescent patients to understand what testing is likely to show and then use testing to validate or refute their expectations. Due to the ease with which samples can be tampered, providers should also carefully refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(49 citation statements)
references
References 29 publications
0
47
0
2
Order By: Relevance
“…2. Urine dipstick tests for the detection of morphine, cannabis, and methamphetamine: According to the American Society for Addiction Medicine (ASAM), drug testing should be used "to discourage nonmedical drug use and diversion of controlled substances, to encourage appropriate entry into addiction treatment, to identify an early relapse, and to improve outcomes of addiction treatment (Hadland and Levy, 2016). Urine dipstick drug tests are practical tools for assessing the relapse in primary care (McDonell et al, 2016).…”
Section: Research Instrumentsmentioning
confidence: 99%
“…2. Urine dipstick tests for the detection of morphine, cannabis, and methamphetamine: According to the American Society for Addiction Medicine (ASAM), drug testing should be used "to discourage nonmedical drug use and diversion of controlled substances, to encourage appropriate entry into addiction treatment, to identify an early relapse, and to improve outcomes of addiction treatment (Hadland and Levy, 2016). Urine dipstick drug tests are practical tools for assessing the relapse in primary care (McDonell et al, 2016).…”
Section: Research Instrumentsmentioning
confidence: 99%
“…Furthermore, the urine test can disclose the presence of the drug in the human body after its clinical effects or blood concentrations have worn off. For example, the detection times for amphetamine are 2–4 days and 12 h in urine and plasma, respectively [ 22 ]. In addition to diagnostic value, the urine paraquat concentration also carries prognostic implication.…”
Section: Discussionmentioning
confidence: 99%
“…Contracting with external providers, such as phlebotomists, lab technicians or nurses, requires greater investment from researchers and risks virus exposure. Research should attempt to define best practices for video-observed urine drug testing which can build on existing processes of in-person observed testing, 36 such as: (1) confirming test cup is intact before collection (eg, twist tops that record number and times of openings), video assessment of bathroom, placement of video device to confirm specimen is collected by individual identified as participant in real-time (use of pH and temperature strips), audio confirmation of micturition, and no use of faucets until visual confirmation the specimen is sealed in tamper-proof container. Although all of this requires additional, creative work on the part of the researchers, it is feasible and has the potential to enhance data collection options for SUD clinical research.…”
Section: Screening Informed Consent and Enrollmentmentioning
confidence: 99%